2017
DOI: 10.5414/cn109198
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietic response to oral iron in patients with nondialysis-dependent chronic kidney disease in the FIND-CKD trial

Abstract: Aims: To evaluate erythropoietic response rates to oral iron over time in iron-deficient anemic patients with nondialysis-dependent chronic kidney disease (ND-CKD). Materials and methods: FIND-CKD was a 1-year, randomized, multicenter trial of iron therapy in patients with ND-CKD, anemia, and iron deficiency, without erythropoiesis-stimulating agent (ESA) therapy. Patients with active infection or C-reactive protein > 20 mg/L were excluded. In this post-hoc analysis, response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…Table 3 summarizes data regarding the impact of inflammation on the effect of OIT versus IIT for IDA in CKD patients, in whom the data for CRP are available. The efficacy of IIT is generally better than OIT for the management of IDA in inflamed ND-CKD patients with positive CRP [ 98 , 118 , 119 , 120 , 121 , 122 ]. Stoves et al showed no significant difference in the Hb levels at the end of OIT and IIT in ND-CKD adults with positive CRP, while the levels of Hb achieved tended to be higher in the IIT group than those in the OIT group [ 123 ].…”
Section: Impact Of Inflammation On Therapeutic Strategy With Iron mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 summarizes data regarding the impact of inflammation on the effect of OIT versus IIT for IDA in CKD patients, in whom the data for CRP are available. The efficacy of IIT is generally better than OIT for the management of IDA in inflamed ND-CKD patients with positive CRP [ 98 , 118 , 119 , 120 , 121 , 122 ]. Stoves et al showed no significant difference in the Hb levels at the end of OIT and IIT in ND-CKD adults with positive CRP, while the levels of Hb achieved tended to be higher in the IIT group than those in the OIT group [ 123 ].…”
Section: Impact Of Inflammation On Therapeutic Strategy With Iron mentioning
confidence: 99%
“…In contrast, Macdougall et al showed that in ND-CKD adults with relatively low CRP levels (mean, 4.5 mg/dL), the response rate to OIT was very limited (21.6%), whereas both low baseline ferritin and CRP may be predictive of the response to OIT [ 121 ]. In addition, serum ferritin levels were higher in HD patients with minor inflammation not responding to IIT than in those responding to IIT and OIT as described in our previous study [ 124 ].…”
Section: Impact Of Inflammation On Therapeutic Strategy With Iron mentioning
confidence: 99%
“…In contrast, a trial evaluating IV versus oral FS in 626 anemic ND-CKD patients, with ID and not receiving ESA therapy, found no difference in the infection rates or cardiac events between patients receiving a higher FCM dose (500–1000 mg/4 weeks), lower FCM dose (200 mg/4 weeks) or oral FS (200 mg/day) during the 56 weeks follow-up (3.9%, 3.3%, and 3.8%, respectively) [66]. It is worth noting that, in this trial, only 21.6% of patients receiving oral iron showed an Hb increase of at least 1 g/dL, and < 30% of early non-responders responded at any subsequent time point during the follow-up, suggesting that the early consideration of alternative therapy would be beneficial in this population [67]. In a cohort of 58,058 HD-CKD patients, IV iron doses greater than 400 mg/month were associated with higher cardiovascular death rates [68].…”
Section: Sucrosomial® Iron For the Management Of Iron Deficiency Imentioning
confidence: 99%
“…There is extensive clinical trial evidence supporting the efficacy of IV iron preparations in patients with both non-dialysis-dependent and end-stage CKD [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ] and patients with CHF [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ], IBD [ 28 , 111 , 112 , 113 , 114 , 115 , 116 , …”
Section: Clinical Use Of IV Ironmentioning
confidence: 99%